Making Inclusion Happen : a Practical Guide. - Hayward, Anne (Sage Publications, 2006)
Teachers often feel overwhelmed by the mountain of DfES guidelines on inclusion. Anne Hayward's practical, accessible book shows them how to implement an effective, high quality inclusion programme. The process is explained in bite size, digestible chunks, and they are given up-to-date information on: -current legislation, Children's Services, Every Child Matters and DfES guidance -a wide range of inclusion programmes and initiatives -planning, managing and implementing inclusion with reference to. Every Child Matters -inspection requirements and self-evaluation strategies -effective inclusion.